RANCANGAN SISTEM PENYEDIAAN STOK BARANG BERBASIS WEB - Dede Supriyadi (Journal of Research and Publication Innovation, 2026)
The Web-Based Stock Provision System Design is a solution to improve the efficiency and effectiveness of inventory management in a company or organization. This system is designed to monitor and manage inventory in real time, thus assisting in more accurate and timely decision-making. With this system, companies can improve their inventory management capabilities, reduce errors and loss of goods, and enhance data security. This system was developed using the SDLC (System Development Life Cycle) system development method and utilizes the PHP programming language and MySQL database. This system offers features such as item data input, stock monitoring, stock reports, and notifications when stock reaches the minimum limit. Furthermore, this system can assist in managing sales and purchase transactions, thereby improving a company's financial management capabilities. This system is expected to improve the efficiency and effectiveness of inventory management, thereby enhancing customer satisfaction and increasing company profits. This system can also help reduce operational costs and increase company productivity. Therefore, this system is very useful for companies or organizations seeking to improve their inventory management capabilities.